Efektifitas Pengembangan Kompetensi Profesional dan Pedagogik Mahasiswa - Suismanto, Suismanto (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2015)
This research reviews about effectiveness of the development of professional and pedagogical student competences, and the recommended to increase the effectiveness of development professional and pedagogical student competences through microteaching activities. This study uses a model CIPP (Context, Input, Process, and Product. The percentage observations converted at the conversion percentage score to the level of effectiveness. Based on the research results obtained that development capabilities pedagogical competence and professional students through microteaching in the Faculty of Tarbiyah and Teaching takes effectively